Reorientation of Religion Curriculum Based on Digital Literacy: Challenges and Opportunities - Caswita Caswita; Inriyani Inriyani; Husni Mubarok; Yanto Maulana Restu; Dodo Murtado (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
The rapid progress of information and communication technology has fundamentally shaken the education system, including Islamic religious education (PAI), which for years has been attached to conventional teaching patterns. This article was prepared to examine how urgent the need is for reorienting the PAI curriculum towards digital literacy, as well as mapping the challenges and opportunities that accompany this process. Using a qualitative approach based on literature study, this research explores, compares, and assembles various relevant literature sources, ranging from journal articles, books, to education policy documents. The findings obtained confirm that reorienting the PAI curriculum towards digital literacy is no longer an option, but rather an urgent need to answer the character of digital native generation students; However, its implementation in the field is still hampered by a number of problems, including the gap in digital competence among teachers, the lack of infrastructure, the reluctance of some parties to move away from the old paradigm, the ethical and security vulnerabilities of religious content in cyberspace, the scarcity of truly credible digital teaching materials, and policy support at the educational unit level which is not yet strong enough.